The Piano and Decentred Cultural Modernity in Korea: Shades of Chopin - Tokita, Alison (Chopin Review, 2023)
This research is situated within the framework laid out in Decentering Musical Modernity (Janz and Yang eds, 2019). Rather than a passive reception of piano music, I avoid ‘triumphalist narratives’, where an individual nation is seen to heroically master Western music. Instead, the piano in Korea is seen as part of a transnational history, largely congruent with that of China, Japan and Taiwan. The global prominence of Korean pianists is obvious from the number of prize-winners in the Chopin Competition. This prominence is an outcome of the active take-up of piano and reed organ from the time of the Korean Empire in the late nineteenth century, associated with missionary activity and the establishment of mission schools. Enthusiasm for the piano and its music continued to grow during the period of Japanese rule (1910–1945), when Japan was also a transmitter of Western music, through its model of school music education, and the advanced musical training provided by Japanese music colleges. This article sketches the history of the piano in Korea during the colonial period, and explores its significance for those aspiring to a global modernity under the conditions of colonial modernity. Attention is given to the steady stream of visiting musicians from metropolitan Japan and Europe between 1920 and 1940 that fed Korea’s piano culture. Also documented are recitals with Chopin repertoire by local pianists who trained in Japan, America and Europe. I argue that East Asia had a common musical modernity, informed by intra-regional flows, which was curiously at odds with the political divisions and conflicts of the time. , colonial modernity, transnational, missionaries, Japanese colonisation